Treatment for chronic depression : cognitive behavioral analysis system of psychoterapy (CBASP) - MacCullough, James P. (New York ; London : Guilford, 2000)
Part I. CBASP and the psychopathology of the patient
A therapist's problems with a chronically depressed patient
Introduction to chronically depressed patients and the CBASP program
Understanding the psychopathology of chronically depressed patients
Course patterns, comorbidity, and psychological characteristics
Part II. CBASP method and procedures
Strategies to enhance motivation for change
Elicitation phase of Situational Analysis
Remediation phase of Situational Analysis
Using the therapist-patient relationship to modify behavior
Measuring acquisition learning and generalized treatment effects
Part III. History and other aspects of CBASP
CBASP emergence on the national scene
Training CBASP psychotherapists
Comparison of CBASP to Beck's cognitive therapy and Klerman's interpersonal psychotherapy models
Resolving common patient problems and crises
Appendices
Appendix A: Therapist prompts for administering Situational Analysis (PASA)
Appendix B: Rating scales for adherence monitoring and for evaluating the quality of the interpersonal relationship
Appendix C: Rating the presence of optimal CBASP therapist qualities and abilities
Str. 295-310:Bibliografija
Kazala
Keywords: kognitivno bihevioralna analiza; depresija